Hospitalization and Mortality in Brazilian Children and Adolescents Due to COVID-19: Retrospective Study - Ana Carolina Pereira de Godoy; Reinaldo Bulgarelli Bestetti (JMIR Pediatrics and Parenting)
Abstract BackgroundCOVID-19 is currently one of the most important medical challenges as it affects the entire population, with children and adolescents being infected as easily as adults. ObjectiveThe objective of this study was to evaluate the prevalence of mortality in children and adolescents aged <19 years, compared to that of adults. MethodsThis retrospective, observational study analyzed the medical records of all patients diagnosed with COVID-19 by real-time reverse transcription–quantitative polymerase chain reaction who were hospitalized at Hospital de Base and the Infant and Maternal Hospital of São José do Rio Preto, São Paulo, Brazil. Out of a total of 8986 hospitalized patients who were COVID-19 positive, 383 (4.26%) were children and adolescents aged <19 years (group 1), and 8603 (95.74%) were adults (group 2). ResultsOverall, mortality was significantly higher (P ConclusionsMortality from COVID-19 in children and adolescents was significantly lower than that in adults and was associated with other comorbidities.